THE IMPACT OF DIGITAL LITERACY PROGRAMS ON STUDENTS' CRITICAL ABILITIES IN VOCATIONAL HIGH SCHOOLS (SMK) - Baso Intang Sappaile (CV. ADIBA AISHA AMIRA, 2025)
This research aims to examine the role of digital literacy in enhancing the critical thinking skills of Vocational High School (SMK) students, with a focus on information analysis, creativity, and problem-solving skills in the technological era. The study was conducted using a systematic literature review method on journal articles, proceedings, books, and research reports published within the last 5–10 years. The analysis results show that digital literacy helps students effectively find, evaluate, and utilize information, as well as improve their ability to identify valid arguments and avoid false information. Additionally, digital literacy serves as a driver of creativity, enabling students to design innovative solutions to real-world problems in vocational fields, including thru the integration of technology in project-based learning. Identified challenges include infrastructure limitations, a lack of teacher training, and the digital divide among students, necessitating strategies to strengthen digital literacy programs in schools. This research recommends developing education policies that support equitable access to technology, enhance teacher competency, and foster cross-sector collaboration to strengthen digital literacy in vocational high schools. These findings are expected to serve as a reference for schools, teachers, and policymakers in designing effective digital literacy programs to equip students with critical thinking and adaptability skills in response to technological advancements.